Banking relationships and access to equity capital markets: Evidence from Japan’s main bank system - Kutsuna, Kenji; Smith, Janet Kiholm; Smith, Richard L. (Journal of Banking & Finance, 2007)
We study the role of banking relationships in IPO underwriting. When a firm in Japan goes public, it can engage an investment bank that is related through a common main bank, or can select an alternative investment bank. The main bank relationship can be an efficient way for the investment bank to acquire information generated by the main bank, but may give rise to conflicts of interest. We find that main bank relationships give small issuers increased access to equity capital markets, but that issuers of large IPOs often switch to non-related investment banks that are capable of managing large offerings. While investment banks seek to exploit bargaining power with related issuers, issuers respond to expected high issue cost by switching to non-related investment banks. The net result is that total issue costs through related and non-related investment banks are similar. With respect to aftermarket performance and use of proceeds, we find no evidence of conflict of interest or self-dealing for either the main bank or the investment bank.